Analysis on the effects of warm up on ankle joint motion and strike patterns for 50m sprint performance - Campana Bonilla, M. V.; Alsowayan, M. N. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to analyze the effects of ankle angles and strike pattern on 50m sprint test performance for young non-athletes. Twenty-seven non-athletes were distributed in a control group (CG) using habitual PE warm up exercises and an experimental group (EG) using basic sprint drills, and performed pre, control and post 50m sprint tests. Motion analysis data from the left leg ankle angle (LAA), right leg ankle angle (RAA) and strike pattern were obtained during landing moments in the sagittal plane using video recording. In accordance with our findings, basic sprint drill warm-ups can improve sprinting time in young girls and contribute to the strengthening of ankle muscles and joints. Motion analysis and the implementation of warm-ups with basic sprint exercises could help in the recognition of range of motion in ankle joints, and benefit sprint performance.